Imaging in alpha-1 antitrypsin deficiency: a window into the disease - Yuh-Chin Tony Huang; Marion Wencker; Bastiaan Driehuys (SAGE Publishing, 2021)
Imaging modalities such as plain chest radiograph and computed tomography (CT) are important tools in the assessment of patients with chronic obstructive pulmonary disease (COPD) of any etiology. These methods facilitate differential diagnoses and the assessment of individual lung pathologies, such as the presence of emphysema, bullae, or fibrosis. However, as emphysema is the core pathological consequence in the lungs of patients with alpha-1 antitrypsin deficiency (AATD), and because AATD is associated with the development of other lung pathologies such as bronchiectasis, there is a greater need for patients with AATD than those with non-AATD-related COPD to undergo more detailed assessment using CT. In the field of AATD, CT provides essential information regarding the presence, distribution, and morphology of emphysema. In addition, it offers the option to quantify the extent of emphysema. These data have implications for treatment decisions such as initiation of alpha-1 antitrypsin (AAT) therapy, or suitability for surgical or endoscopic interventions for reducing lung volume. Furthermore, CT has provided vital insight regarding the natural history of emphysema progression in AATD, and CT densitometry has underpinned research into the efficacy of AAT therapy. Moving forward, hyperpolarized xenon gas ( 129 Xe) lung magnetic resonance imaging (MRI) is emerging as a promising complement to CT by adding comprehensive measures of regional lung function. It also avoids the main disadvantage of CT: the associated radiation. This chapter provides an overview of technological aspects of imaging in AATD, as well as its role in the management of patients and clinical research. In addition, perspectives on the future potential role of lung MRI in AATD are outlined.